Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/inf.0000000000003135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of a Cohort of Pediatric Oncohematologic Patients With COVID-19 Infection in the City of Bogotá, Colombia

Abstract: Background:In children, the complications of severe acute respiratory syndrome coronavirus 2 infection occur less frequently than in adults but the characteristics of this disease in oncology patients are not well characterized. Methods: This was a retrospective study in patients younger than 18 years of age with coronavirus disease 2019 (COVID-19) and cancer diagnoses between April and September 2020. Demographic variables, laboratory, and radiologic findings and complications of each case were identified. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
(54 reference statements)
1
13
1
Order By: Relevance
“…Several previous reports have suggested that pediatric patients with cancer, infected with COVID-19, are at an increased risk of severe disease due to their underlying malignancy and treatment effect, similar to adults with cancer [ 16 ]. Pediatric patients with cancer who test positively for COVID-19 have been reported to require intensive care admission and to have unfavorable outcomes [ 17 , 18 ]. Continued chemotherapy during COVID-19 infection has been reported to result in dismal outcomes [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous reports have suggested that pediatric patients with cancer, infected with COVID-19, are at an increased risk of severe disease due to their underlying malignancy and treatment effect, similar to adults with cancer [ 16 ]. Pediatric patients with cancer who test positively for COVID-19 have been reported to require intensive care admission and to have unfavorable outcomes [ 17 , 18 ]. Continued chemotherapy during COVID-19 infection has been reported to result in dismal outcomes [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients with cancer who test positively for COVID-19 have been reported to require intensive care admission and to have unfavorable outcomes [ 17 , 18 ]. Continued chemotherapy during COVID-19 infection has been reported to result in dismal outcomes [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five patients (7.0%) died during the period of observation, one with ALL (no further details) [ 33 ], one with osteosarcoma and extensive pulmonary metastases [ 34 ], 2 with COVID-19-related multiorgan failure after SCT and CAR-T-cell therapy [ 23 ], and one patient with neuroblastoma [ 35 ]. Additionally, 15 deaths of SARS-CoV-2-positive pediatric cancer patients were reported without mentioning the underlying malignancy [ 38 – 41 ] and 5 deaths related to SARS-CoV-2 associated complications additive to refractory ALL [ 36 , 37 ] were reported.…”
Section: Resultsmentioning
confidence: 99%
“…The global characteristics and outcomes of SARS-CoV-2 infection in children and adolescents with cancer (GRCCC) reported that the all-cause mortality in that study was 6.3%, ranging from 11% in low-middle income countries to 6% in upper-middle income countries ( 21 ). The mortality attributed to COVID-19 in this population reported by multiple studies from different countries in Latin America ranged from 6 to 12.3% ( 28 31 ). A study by Shahid et al performed in Pakistan, included 161 cancer patients with and without COVID-19 and compared their outcomes, finding a mortality of 6.8% in COVID-19 patients vs. 2.7% non-COVID-19 patients ( 32 ).…”
Section: Discussionmentioning
confidence: 84%